Penerapan Metode Time Cost Trade Off (TCTO) pada Proyek Pembangunan Peningkatan Gedung Dinas Pekerjaan Umum Kota Balikpapan - Nadhilah Nur Ramadhan; Gunaedy Utomo; Reno Pratiwi (Universitas Batanghari Jambi, 2026)
Delays in project work can be anticipated by accelerating its implementation. In accelerating the project, it must be well planned by using various acceleration alternatives. Alternatives that can be used to accelerate the project are by adding working hours, adding labor, or a combination of both. The purpose of this study is to analyze the application of the Time Cost Trade Off method with alternative acceleration of adding working hours and alternative acceleration of adding labor. The method used is a case study on the Balikpapan City Public Works Department Building Improvement Construction Project with a duration of 174 calendar days by finding the critical path using Microsoft Project and then crashing to obtain the cost slope of activities on the critical path. The results of this study obtained the optimal alternative is the acceleration alternative of adding the number of crashing 3 labor with the duration required to complete the project is 68.89 days at a cost of Rp7.770.887.756. which is the acceleration alternative that has the lowest cost of other acceleration alternatives.